1994
DOI: 10.1210/jcem.79.4.7962275
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of dexamethasone-induced insulin resistance in healthy humans.

Abstract: Insulin resistance may result from decreased muscle blood flow, impaired cellular glucose transport, or intracellular deficits of glucose metabolism. The mechanisms responsible for dexamethasone-induced insulin resistance were investigated in healthy human subjects. During a 2-h hyperinsulinemic clamp, dexamethasone decreased glucose uptake, oxidation, and nonoxidative glucose disposal during the first hour. During the second hour, glucose uptake was normalized by means of hyperglycemia; glucose oxidation, how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
57
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 22 publications
9
57
1
Order By: Relevance
“…[36][37][38] Glucocorticoids also may affect lipolysis by permissive effects modulating responsiveness to lipolytic hormones, such as catecholamines and growth hormone. 37,39,40 Although dexamethasone may stimulate lipolysis, the missing increase in posttreatment NEFA concentrations in the present and other studies 2,3,33 may be explained by concurrent increase in hepatic lipid oxidation 10 For statistical analysis, see Table 2. tissues to meet energy requirements in a state of decreased insulin sensitivity and decreased glucose uptake. 41 The lack of effect of dexamethasone on mean plasma BHB concentrations in this study is in agreement with results reported previously.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…[36][37][38] Glucocorticoids also may affect lipolysis by permissive effects modulating responsiveness to lipolytic hormones, such as catecholamines and growth hormone. 37,39,40 Although dexamethasone may stimulate lipolysis, the missing increase in posttreatment NEFA concentrations in the present and other studies 2,3,33 may be explained by concurrent increase in hepatic lipid oxidation 10 For statistical analysis, see Table 2. tissues to meet energy requirements in a state of decreased insulin sensitivity and decreased glucose uptake. 41 The lack of effect of dexamethasone on mean plasma BHB concentrations in this study is in agreement with results reported previously.…”
Section: Discussionmentioning
confidence: 61%
“…Almost the same result was described in healthy humans after dexamethasone treatment (decrease to 10 and 20% of baseline for untreated and treated subjects, respectively). 10 In vitro studies using human adipocytes assume a direct influence of glucocorticoids on expression of proteins involved in lipolysis, but the results still are inconsistent. [36][37][38] Glucocorticoids also may affect lipolysis by permissive effects modulating responsiveness to lipolytic hormones, such as catecholamines and growth hormone.…”
Section: Discussionmentioning
confidence: 99%
“…Dexamethasone induces substantial insulin resistance in other species by several mechanisms (McMahon et al 1988). Glucocorticoids oppose the actions of insulin in the liver by promoting gluconeogenesis (McMahon et al 1988) and act peripherally in muscle and adipose tissue to inhibit glucose uptake (Tappy et al 1994) and decrease glycogen synthesis (Coderre et al 1992). Corticosteroids reduce glucose uptake in rat skeletal muscle by decreasing insulin-stimulated phosphorylation of tyrosine kinase without affecting the number or affinity of insulin receptors for insulin (Coderre et al 1992).…”
Section: Corticosteroidsmentioning
confidence: 99%
“…In rats, administration of cortisol increased plasma levels of pyruvate and impaired pyruvate tolerance, suggesting a decrease in the rate of pyruvate oxidation in the tissues [15]. In man, administration of dexamethasone decreased whole-body insulinstimulated glucose oxidation (measured with glucose-insulin clamps and indirect calorimetry) ; this decrease was considered secondary to the increase in plasma levels of non-esterified fatty acids [42]. Previous studies have shown that glucocorticoids increase the rate of lipolysis, suggesting that insulin resistance in muscle may be caused by the increased oxidation of non-esterified fatty acids [17,43].…”
Section: Figure 4 Rates Of Lactate Formation At Various Concentrationmentioning
confidence: 99%